ANALISIS KINERJA PENGELOLAAN KEUANGAN PEMERINTAH PROVINSI JAWA TIMUR TAHUN 2008-2013 - Tripitono Adi Prabowo (Trunojoyo University of Madura, 2013)
This study analyzes the financial performance of the province of East Java in2008 until 2013. Through a quantitative approach, this study describes the degree of fiscal decentralization, fiscal independence and activity ratios East Java provincial budget in 2008 until 2013. The results showed that: the performance of financial management of East Java Province has been very good, although the ratio of expenditure activity showed a dominance ratio of indirect expenditure on direct spending. Thus, the recommendation to the Government of East Java are: 1)To accelerate SKPD and other related agencies to increase revenue, 2)Provide a planning on budgeting for autonomous regions based on the needs of real people in East Java and in accordance with the mission and the mission of the Governor and Deputy Governor of East Java, 3)To increase the ratio of direct expenditure to total expenditure.